Inventory Control Using Forcasting Method: Moving Average and Exponential SmoothingForcasting - Riki Riki; Stefanus Stefanus (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2020)
Analysis and Design of Inventory Control Information Systems using the Forcasting method in order to minimize errors in providing stock items, and increase sales in a cost efficient manner so as not to waste more costs. The method used is to use 2 (two) modules, namely: Single Moving Average and Single Exponential Smoothing which are used in the forecasting calculation process to determine future stock of goods and have a connection with the system. By analyzing sales data that is in order to minimize errors in excess stock of goods that waste extra costs. By using 2 (two) modules we can estimate the items that will be in stock and the results will be summarized in the report.